A Bulla of ʾӐdōnîyāhû, the One Who Is Over the House, from beneath Robinson's Arch in Jerusalem. (2nd January 2022) - Vanderhooft, David S.; Richey, Madadh; Shukron, Eli
Abstract : The present paper publishes a new, nearly complete bulla excavated in 2013 beneath Robinson's Arch in Jerusalem. It was first identified in 2019 during sifting of soil excavated from a Roman-era drainage channel. The bulla belonged to a Judahite government official, 'the One Who Is Over the House'. The excavation of this bulla validates the authenticity of several other bulla bearing the same legend and clarifies both epigraphic and biblical attestations of the title 'the One Who Is Over the House'.